Floral visitor diversity of ruderal plants in San Gerardo de Dota, Costa Rica: a highland agricultural-natural landscape - Rojas-Malavasi, Geovanna (2025)
Introduction: Wild plants rely mainly on insects for pollination, and many of these plants are essential to maintaining a diverse and abundant community of crop insect-pollinators. In Costa Rican highland ecosystems, the diversity and abundance of insect floral visitors have been poorly studied, despite their importance and proximity to crops in this area. Objective: to determine the richness and composition of floral visitor insect species of native and ruderal herbaceous plants close to cultivated areas in San Gerardo de Dota, Costa Rica. Methods: We systematically collected flower-visiting insects along transects in two different sites and identified them to the lowest taxonomic level. We estimated alpha diversity for each season and 11 plant groups created specifically for this study. We defined these plant groups based on flower morphology, life history traits, and their taxonomic relatedness. We also compared the insect community composition across seasons and plant groups. Results: We collected a total of 1306 insects, mainly flies (Diptera), from 62 families on 46 plant species during 12 sampling visits. Insect diversity (alpha diversity) increased during the rainy season, possibly because resources (e.g., food and reproductive sites) for flies increase during this season. Insect species composition varied among plant groups. The most abundant insect communities overlapped extensively among plant groups, but other communities compose mainly by some tachinids, chloropids and wasps did not overlap between other plant groups.   Conclusion: Seasonal differences in flower-visiting insects could be attributed to a greater availability of resources during the rainy season. Differences in the composition of visitor insects across plant groups were likely influenced by temporal variation in blooming of the different plant groups, blooming intensity, and flower traits. To preserve the rich diversity of floral visitors and the pollination services they provide, a diverse array of ruderal plants must be maintained.